Analisis Indeks dalam Menilai Kinerja Keuangan PT. Cisarua Mountain Dairy Tbk Tahun 2022-2025 - Neneng Mulyaningsih; Habil Febrian (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the financial performance of PT Cisarua Mountain Dairy Tbk for the period 2012–2025 using the Index method. This method was chosen to evaluate the company's financial composition by comparing each balance sheet report item to the item in the base year in the form of a percentage. The research data is in the form of balance sheet financial statements obtained from the official website of the Indonesia Stock Exchange. The research model used is qualitative descriptive by utilizing secondary data. The data collection technique is carried out through documentation, while the data analysis uses Sugiyono's theory as a methodological foundation. The results of the analysis show that the overall financial condition of PT Cisarua Mountain Dairy Tbk is relatively stable throughout the research period. The stability was supported by a strong capital structure and significant operational management, despite the company's dynamic economic challenges. These findings confirm that the application of the Index method can provide a clear picture of the consistency of the company's financial performance, as well as a reference for management in formulating more effective asset and capital management strategies to maintain business sustainability in the future.